HUBUNGAN ADAPTASI PETANI TERHADAP PERUBAHAN IKLIM DENGAN PRODUKTIVITAS TEMBAKAU PADA LAHAN SAWAH DAN TEGALAN DI KABUPATEN JEMBER - Herminingsih, Hesti (Jurnal Sosial Ekonomi Pertanian, 2014)
Climate change hasa huge impact for tobacco in Jember Regency. This study aims to determine 1) the level of productivity of tobacco on field and moor in Jember Regency; 2) the wayadaptation that has beentaken bytobaccofarmersto face theclimatechange 3) The correlation of adaptation by tobacco farmers toward the levelof productivity of tobaccoo field and moor. The method used in this research is a mixed qualitative and quantitative methods. The result shows1) productivity of tobacco on moor is 1.4 tons/ha and on moor is 1.2 ton/ha, 2) The adaptations of tobacco farmers to the face of climate change are; planting schedule planning, determination and prediction of weather, increasethe capital, changes in tillage techniques, change inputs, changes in the number of labor, anticipation droughts and heavy rainfall, 3) Adaptation that has significant correlation to productivity tobacco farmers on moor is the determination and prediction of weather, changes in tillage techniques, changes in the number of labor and anticipation of high rainfall. While in the fields adaptation that has significant correlation to productivity tobacco farmers ischanges tillage techniques. Keywords: Climate, adaptation, productivity of tobacco